Work stress, burnout and mental health of academic staff during the online teaching due to the Covid-19 pandemic - Berezina, Elizaveta *; Chin, Yue Xin (ACM Digital Library, 2022)
This study aims to identify the relationship between work stress, burnout and mental health of academic staff during the implementation of the Movement Control Order (MCO) when the only possible mode of teaching was the fully online mode. It has been hypothesized that there are significant relationships between work stress and mental health among academics; and work stress (work overload, role ambiguity, lack of autonomy) can predict a significant amount of the variance in mental health (anxiety/insomnia, social dysfunction) of academic staff during the online teaching, after taking the possible effect of burnout into consideration. This study involved 106 academic staff (73 females, 33 males) to complete an online survey which included the Work Stress Scale, Burnout Measure, and General Health Questionnaire 28. The findings of this study showed the significant positive relationships between all variables of work stress and mental health; work overload and burnout predicted anxiety/insomnia; lack of autonomy and burnout predicted social dysfunction. These findings have implications for Human Resources practices in efforts in reducing work stress and improving mental health of academic staff during these trying times.